2018
DOI: 10.4314/ahs.v18i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis and intervention for autism spectrum disorder in Africa: insights from a case study

Abstract: BackgroundGlobally the prevalence of autism spectrum disorder (ASD) has become more apparent. Prevalence on the African continent remains unknown. There is a call for further research into ASD in Africa as well as means to make early diagnosis and intervention possible.ObjectivesThe study aimed to raise awareness about ASD in Africa and encourage dialogue on possible intervention strategies for ASD in low resource settings.MethodsThis was a qualitative mixed method case study. Literature regarding ASD in Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…These findings show a high level of knowledge when compared to a prior survey conducted in Saudi Arabia, which found that the degree of understanding was only 41% [ 29 ]. One study in Australia and another in Africa found similar results to ours; in both studies, participants had a general understanding of ASD but very little understanding of the disease’s cause [ 30 , 31 ]. The majority of Australians were aware of ASD, but they believed it was caused by the MMR vaccine.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings show a high level of knowledge when compared to a prior survey conducted in Saudi Arabia, which found that the degree of understanding was only 41% [ 29 ]. One study in Australia and another in Africa found similar results to ours; in both studies, participants had a general understanding of ASD but very little understanding of the disease’s cause [ 30 , 31 ]. The majority of Australians were aware of ASD, but they believed it was caused by the MMR vaccine.…”
Section: Discussionsupporting
confidence: 80%
“…However, the World Health Organization (WHO) stated that there was no evidence linking any vaccine to autism [ 19 , 30 ]. Another study revealed a misunderstanding about the treatment, with participants believing that children with ASD are unable to attend public school [ 31 ]. As previously said, this disorder is caused by a number of variables, some of which are genetic in nature and others which are environmental in nature [ 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO), on the other hand, said that no evidence linking any vaccine to autism exists [ 30 ]. Another study found that participants misunderstood the treatment, believing that children with ASD are unable to attend public school [ 31 ]. As previously said, a variety of factors contribute to the development of this condition, some of which are genetic in origin and others which are environmental in nature [ 15 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously said, a variety of factors contribute to the development of this condition, some of which are genetic in origin and others which are environmental in nature [ 15 , 32 ]. In another African study, not just among communities but also among health care providers and educators, there was a lack of understanding [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keeping with the mental health theme, we bring you a paper on early diagnosis and intervention for autism spectrum disorder. 17 The NCD section ends with a case report on Truncus arteriosus communis. 18 …”
Section: Non-communicable Diseasesmentioning
confidence: 99%